Collision induced broadening and shifting of the H and K lines of Ca+ at low temperature. (September 2017) - Wang, Xin; Zhang, Rui; Shen, Yong; Liu, Qu; Zou, Hongxin; Yan, Bing
Highlights: The PECs of the Λ-S states correlating with lowest three atomic limits in Ca + -He molecular system have been calculated. The SOC have been considered and the PECs of Ω states are obtained. Collision induced broadening and shifting of the H and K lines of Ca + by He atoms at low temperature have been computed with Anderson–Talman theory. Abstract: Multireference configuration interaction method was used to compute the potential energy curves of Λ-S states correlating with lowest three atomic limits in Ca + -He molecular collision system. The potential energy curves of nine Ω states were obtained with inclusion of spin-orbit coupling. And the electric dipole and quadrupole moment matrix elements between excited states and ground state were also computed. Furthermore, with aid of the Anderson–Talman theory we calculated the broadening and shifting coefficients for Ca + -He spectral lines in the low temperature regime. For H line, α = 0.303 × 10 −20 cm −1 /cm −3, β = −0.0527 × 10 −20 cm −1 /cm −3 ; For K line, α = 0.233 × 10 −20 cm −1 /cm −3, β = −0.0402 × 10 −20 cm −1 /cm −3 These results are helpful to understand the collision effects induced by He atom in further spectra investigations of cold Ca + ions.